PROFIL KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPA KELAS IV SDN TEGAL BESAR 02 JEMBER - Nur Illah Merdiana; Mely Pitasari; Prima Cristi Crismono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to evaluate the critical thinking skills of fourth-grade students at SDN Tegal Besar 02 in Science (IPA) lessons, with a focus on the topic of force. The method used is a descriptive qualitative approach, which collects data thru a written test consisting of 10 essay questions based on critical thinking criteria according to Ennis. Researchers also conducted interviews with the subject teachers. The findings of this study indicate that students' critical thinking skills vary, with the majority falling into the low to medium category. The elementary clarification and basic support aspects are in the moderate category, while abilities in the inference, advanced clarification, and strategy and tactics aspects are still considered low. Additionally, researchers found that learning motivation, whether stemming from external or internal factors, plays a significant role in critical thinking skills. The students' own lack of motivation and the lack of support from their surroundings can hinder the learning process. Therefore, the research also found the importance of implementing varied, interactive, and contextual learning methods at the primary education level, accompanied by efforts to increase students' intrinsic and extrinsic motivation, so that critical thinking skills can develop optimally in science learning and help students face future educational challenges.